Relationship between Career Competencies and Career Readiness: The Role of Career Guidance Services - Michael Ampadu_Asiamah; Jocelyn Viray (Journal of Counseling and Educational Research, 2026)
Career guidance services play crucial role in the lives of students in the second cycle institutions. This research aims to explore the relationship between the career competencies and career readiness of students. The research method used was a quantitative design with 69 questions. Out of a population of 4592 students, 420 respondents were selected, using random sampling techniques experimental design. Descriptive Correlational data were analyzed using Levene's Test for Equality of Variances, T-tests, and Pearson r in SPSS 25. The results of the hypothesis test shows a significance level of 0.001 <0.05, thus rejecting H0 and accepting Ha. The correlation coefficient value of r = 0. 636 indicate a marked relationship between the variables. The study concludes that there is a significant relationship between career competencies and career readiness under the career guidance services. These findings are beneficial for the institutions because they will enhance their career guidance services.